2017
DOI: 10.1167/iovs.16-20957
|View full text |Cite
|
Sign up to set email alerts
|

Micrometric Control of the Optics of the Human Eye: Environment or Genes?

Abstract: There is a significant genetic contribution to the variance of aberrations of the eye, not only at macroscopic levels, as in myopia or astigmatism, but also at microscopic levels, where a few micrometers changes in surface topography can produce a large difference in the value of the optical aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Hammond et al 12 reported that nearly half of the variance of astigmatism can be explained by genetic reasons. Furthermore, Tabernero et al 13 investigated whether corneal aberrations are genetically or environmentally determined by analyzing 138 eyes of 69 twins. They confirmed that genes play an important role in the variance of corneal aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hammond et al 12 reported that nearly half of the variance of astigmatism can be explained by genetic reasons. Furthermore, Tabernero et al 13 investigated whether corneal aberrations are genetically or environmentally determined by analyzing 138 eyes of 69 twins. They confirmed that genes play an important role in the variance of corneal aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed that genes play an important role in the variance of corneal aberrations. For instance, the heritability of corneal spherical aberration was reported to be 52%, 13 while a prior Korean population-based study identified 20%. 14 Intraocular pressure is considered as another factor affecting the development of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…We found a high prevalence of low and moderate myopia in a sample of young twins (average year of birth was 1995.8 ± 3.0). A previous similar study was performed in a sample of twins born in the same geographical area, with an average age at the moment of the measurements (2014) of 54.9 ± 6.3 years (average year of birth was 1958.3 ± 6.7) 34,40 . On average, their manifest refraction gave a SE that was emmetropic (0.0 ± 1.4 D) for the MZ twins, and slightly hyperopic (+0.5 ± 1.6 D) for the DZ twins.…”
Section: Discussionmentioning
confidence: 97%
“… 35 In a twin study of Tabernero et al. 36 the authors found that genetic factors contribute up to 52% for spherical aberration development. Another important factor for corneal shape development is intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%